Pengaruh Profitabilitas dan Leverage Terhadap Kualitas Laba - Dian Maulita; Santi Oktaviani; Nafiudin Nafiudin (Sains Manajemen: Jurnal Manajemen Unsera, 2022)
This study aims to examine the effect of profitability as measured by the Return On Assets (ROA) proxy and Leverage as measured by the Debt to Equity Ratio (DER) proxy on earnings quality. This study uses a quantitative method with an associative research design that is causal in nature. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange. 2017-2019. The total population in this study were 193 companies. The sampling method in this study used the company purposive sampling method which complied with the company being a sample of 94 with 3 years of observation. Data collection techniques using literature and documentation. The data analysis technique uses multiple linear regression using SPSS software. The results of this study indicate that profitability has an effect on earnings quality while leverage has no effect on earnings quality. The results of this study can be used as a reference in the field of finance. The limitations of this study only examine two variables that affect earnings quality. It is hoped that in subsequent research, add or use other independent variables that can affect earnings quality, such as liquidity, profit growth, dividend policy, accounting conservatism and so on.